Long-range transport influence on key chemical components of PM2.5 in the seoul metropolitan area, south korea, during the years 2012-2016 - Bae, Changhan; Kim, Byeong Uk; Kim, Hyun Cheol; Yoo, Chul; Kim, Soontae (Atmosphere, 2020)
This study identified the key chemical components based on an analysis of the seasonal variations of ground level PM2.5 concentrations and its major chemical constituents (sulfate, nitrate, ammonium, organic carbon, and elemental carbon) in the Seoul Metropolitan Area (SMA), over a period of five years, ranging from 2012 to 2016. It was found that the mean PM2.5 concentration in the SMA was 33.7 μg/m3, while inorganic ions accounted for 53% of the total mass concentration. The component ratio of inorganic ions increased by up to 61%-63% as the daily mean PM2.5 concentration increased. In spring, nitrate was the dominant component of PM2.5, accounting for 17%-32% of the monthly mean PM2.5 concentrations. In order to quantify the impact of long-range transport on the SMA PM2.5, a set of sensitivity simulations with the community multiscale air-quality model was performed. Results show that the annual averaged impact of Chinese emissions on SMA PM2.5 concentrations ranged from 41% to 44% during the five years. Chinese emissions' impact on SMA nitrate ranged from 50% (winter) to 67% (spring). This result exhibits that reductions in SO2 and NOX emissions are crucial to alleviate the PM2.5 concentration. It is expected that NOX emission reduction efforts in China will help decrease PM2.5 concentrations in the SMA.
Keywords: Chemical component; Chemical constituents; Community multi-scale air quality models; Emissions' impacts; Long range transport; PM2.5 concentration; Sensitivity Simulation; Seoul metropolitan area; Chemical composition; Long-range transport; Nitrate; PM2.5; SMA; Sulfate